Edukasi Anatomi Tubuh untuk Anak Usia Dini di Desa Mancasan - Taufik Eko Susilo; Ouwada Aiko Suda; Tiara Fatmarizka; Farid Rahman; Qonitah Faizatul Fitriyah; Hillyatul Millah; Shafa Oktavia Nafisah; Syahrul Hilbram Julanar (LPMP Imperium, 2025)
The introduction to human anatomy program for early childhood held in Mancasan Village on Thursday, October 31, 2024, was a collaboration between the Physiotherapy and Early Childhood Education (PAUD) programs of Universitas Muhammadiyah Surakarta. This program aimed to enhance the understanding of 20 children about human anatomy in an interactive and enjoyable way, while also empowering 5 PAUD teachers to implement creative teaching methods. Utilizing the educational application Jelajah Tulang, the activities included play-based learning methods, visual games, interactive songs, and sensory activities. Evaluation results indicated that the program successfully increased children’s enthusiasm and understanding of anatomy, while providing valuable training for PAUD teachers. However, challenges such as limited access to technology and program duration remain obstacles to the sustainability of the initiative.